The Impact of Affective Commitment to Organizational Citizenship Behavior on Millennial Employees in an Indonesian Construction Company: Work Engagement and Knowledge Sharing as Mediators - Prayitno, Sahri; Iqbal, M. Ali; Aulia, Irfan Noviandy (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This research aimed to find out the direct impact of Affective Commitment on OCB, Work Engagement, and Knowledge Sharing and indirectly between Affective Commitment and OCB mediated by Work Engagement and Knowledge Sharing. Methodology/approach – The research is causal quantitative with the population are the millennial employees in one of Indonesia’s construction companies, with a sample of 287 employees. The research uses SEM PLS data analysis by SmartPLS 3.0. Findings – The results show a positive impact and significant from the direct effect between Affective Commitment and OCB, Affective Commitment and Work Engagement, Affective Commitment and Knowledge Sharing, Work Engagement and OCB, also Knowledge Sharing and OCB. Then, the indirect effect between Affective Commitment to OCB mediated by work engagement and knowledge sharing also has a positive impact and significan, with the mediating effect provided being complimentary. Novelty/value – Based on the results of the analysis, it was found that these two mediating constructs succeeded in mediating the relationship between Affective Commitment to OCB. Although Work Engagement has a stronger mediating effect than Knowledge Sharing, these two mediating constructs have succeeded in providing complementary effects